Теоретическая значимость понимания прочитанного в умозаключениях учащихся - Sobirov , Jasur (The Lingua Spectrum, 2025)
This work explores strategies for teaching students how to draw conclusions during reading as part of an effective reading comprehension strategy. The work also outlines a series of practical steps for educators to guide students in the process of understanding, analyzing, and summarizing texts. Key approaches discussed include setting clear reading goals, identifying main ideas, encouraging critical questioning, and synthesizing information. The work emphasizes the importance of fostering independent thinking by helping students relate new information to their prior knowledge and personal experiences.